Two-photon patterned photostimulation with low-power, high-efficiency and reliable single-cell optogenetic control - Wang, Yifan; Zheng, Yao; Xu, Yongxian; Li, Rongrong; Zheng, Yameng; Chen, Jiajia; Li, Xiaoming; Hu, Hailan; Duan, Shumin; Gong, Wei; Si, Ke (bioRxiv, 2022)
Two-photon optogenetics enables selectively stimulating individual cells for manipulating neuronal ensembles. As the general photostimulation strategy, the patterned two-photon excitation has enabled millisecond-timescale activation for single or multiple neurons, but its activation efficiency is suffered from high laser power due to low beam-modulation efficiency. Here, we develop a high- efficiency beam-shaping method based on the Gerchberg-Saxton (GS) algorithm with spherical-distribution initial phase (GSSIP) to reduce the patterned two-photon excitation speckles and intensity. It can well control the phase of shaped beams to attain speckle-free accurate patterned illumination with an improvement of 44.21% in the modulation efficiency compared with that of the traditional GS algorithm. A combination of temporal focusing and the GSSIP algorithm (TF-GSSIP) achieves patterned focusing through 500-μm-thickness mouse brain slices, which is 2.5 times deeper than the penetration depth of TF-GS with the same signal-to-noise ratio (SNR). With our method, the laser power can be reduced to only 55.56% of that with traditional method (the temporal focusing with GS, TF-GS) to reliably evoke GCaMP6s response in C1V1-expressing cultured neurons with single-cell resolution. Besides, the photostimulation efficiency is remarkably increased by 80.19% at the same excitation density of 0.27 mW/μm2. This two-photon stimulation method with low-power, reliable and patterned illumination may pave the way for analyzing neural circuits and neural coding and decoding mechanism.